Analysis of genetic variability for retention of kernel carotenoids in sub-tropically adapted biofortified maize under different storage conditions. (May 2020) - Dutta, Suman; Muthusamy, Vignesh; Hossain, Firoz; Baveja, Aanchal; Chhabra, Rashmi; Jha, Sunil K.; Yadava, Devendra K.; Zunjare, Rajkumar U.
Abstract: Mutant crtRB1 gene has contributed to provitamin-A (proA) rich maize cultivars worldwide. However, considerable degradation of proA during storage reduces its efficacy. Here, 22 biofortified inbreds with crtRB1 were stored for 6-months. Refrigerated and vacuum storage were significantly better than traditional storage for retention of both proA and non-proA carotenoids. Under traditional storage, β-cryptoxanthin (20.7%) had higher retention than β-carotene (16.3%), while lutein (53.9%) had better retention over zeaxanthin (42.4%) among crtRB1- inbreds. Major fraction of proA (68.8%) was lost during first three months of storage, while non-proA showed slow and progressive degradation (3-months: 28.5% loss, 6-months: 49.4% loss) under traditional storage. HKI161PV (27.4%), HP465-41 (26.9%), HKI193–1 PV (25.9%) and HP465-30 (25.7%) were the most potential inbreds with >25% retention of proA compared to 8–10% retention among crtRB1 -based inbreds. Promising inbreds can be used as donor in biofortification programme, while contrasting inbreds distinctly differing for retention of proA carotenoids can be used to map loci for higher retention of proA. Graphical abstract: Image 1 Highlights: Major fraction of proA is degraded in first three months of traditional storage. Significant genetic variation was observed for retention of proA under storage. β-cryptoxanthin had better retention than β-carotene among proA carotenoids. Inbreds with high retention for proA can be used as donor in breeding programmes.